Review: From Lapland to Sápmi: Collecting and Returning Sámi Craft and Culture - Amy Furness; Megan Macken; Terrie Wilson (Art Libraries Society of North America, 2023)
Book review of From Lapland to Sápmi: Collecting and Returning Sámi Craft and Culture by Barbara Sjoholm. University of Minnesota Press, March 2023. 352 p. ill. ISBN 978-1-5179-1197-3 (h/c), $34.95. https://www.upress.umn.edu/book-division/books/from-lapland-to-sa-pmi. Reviewed July 2023 by Amy Furness, Head, Library & Archives, Art Gallery of Ontario, amy.furness@ago.ca.